2011
DOI: 10.1088/0004-637x/741/1/49
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Sample of Ultraluminous X-Ray Source Host Galaxies

Abstract: One hundred seven ultraluminous X-ray (ULX) sources with 0.3−10.0 keV luminosities in excess of 10 39 ergs s −1 are identified in a complete sample of 127 nearby galaxies. The sample includes all galaxies within 14.5 Mpc above the completeness limits of both the Uppsala Galaxy Catalog and the Infrared Astronomical Satellite survey. The galaxy sample spans all Hubble types, a four decade range in mass, 7.5 < log(M/M ⊙ ) < 11.4, and in star-formation rate, 0.0002 < SFR(M ⊙ /yr) ≤ 3.6. ULXs are detected in this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
285
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(327 citation statements)
references
References 51 publications
39
285
3
Order By: Relevance
“…As can be seen by comparing Figure 2 We estimate the flux of each 3σ-detected source assuming a power law with a photon index of Γ = 1.7 (Swartz et al 2004;Soria 2011). Their luminosities (Table 1) put them in the range of ultra-luminous X-ray sources (ULXs; commonly associated with star forming galaxies Swartz et al 2011;Luangtip Figure 2. (a) Extraction regions for both bright point-like sources W1-3, E1-5, and B1 associated with the southwestern galaxy UGC 12914, northeastern galaxy UGC 12915, and the bridge region, respectively; and the extended regions extracted (see Table 1).…”
Section: The Compact Sourcesmentioning
confidence: 99%
“…As can be seen by comparing Figure 2 We estimate the flux of each 3σ-detected source assuming a power law with a photon index of Γ = 1.7 (Swartz et al 2004;Soria 2011). Their luminosities (Table 1) put them in the range of ultra-luminous X-ray sources (ULXs; commonly associated with star forming galaxies Swartz et al 2011;Luangtip Figure 2. (a) Extraction regions for both bright point-like sources W1-3, E1-5, and B1 associated with the southwestern galaxy UGC 12914, northeastern galaxy UGC 12915, and the bridge region, respectively; and the extended regions extracted (see Table 1).…”
Section: The Compact Sourcesmentioning
confidence: 99%
“…The first source is located in a star-forming region of the galaxy classified as a late-type dwarf spiral at a distance of 6.8 Mpc (Drozdovsky & Karachentsev 2000). The source NGC 5474 X-1 is identified as a ULX by Swartz et al (2011), with an X-ray luminosity of LX ≃ 1.4× 10 40 erg s −1 . The second ULX is located on the edge of the disc of M66, which is an SAb-type barred galaxy at a distance of 10.6 Mpc (Lee & Jang 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such low metallicities are required in order to make more massive BHs (e.g., Heger et al 2003), which shows that it would be possible for ULXs to be massive stellar remnant BHs. Yet, population studies of the HMXB population of the local universe has also revealed an unbroken power-law slope in the XLF up to ∼ 2 × 10 40 erg s −1 (e.g., Grimm et al 2003;Swartz et al 2011;Mineo et al 2012). This continuation indicates that the majority of ULXs with L X < 2 × 10 40 erg s −1 are likely to be HMXBs with a stellar-mass BH accreting at around or above the Eddington limit.…”
Section: Introductionmentioning
confidence: 99%